2022
DOI: 10.1126/sciadv.abq7240
|View full text |Cite
|
Sign up to set email alerts
|

BCG vaccinations drive epigenetic changes to the human T cell receptor: Restored expression in type 1 diabetes

Abstract: The BCG (Bacille Calmette-Guérin) vaccine, introduced 100 years ago for tuberculosis prevention, has emerging therapeutic off-target benefits for autoimmunity. In randomized controlled trials, BCG vaccinations were shown to gradually improve two autoimmune conditions, type 1 diabetes (T1D) and multiple sclerosis. Here, we investigate the mechanisms behind the autoimmune benefits and test the hypothesis that this microbe synergy could be due to an impact on the host T cell receptor (TCR) and TCR signal strength… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 74 publications
0
8
0
Order By: Relevance
“…Vaccines have been shown to have heterologous, or ‘non-specific’ effects, which are additional effects beyond the specific protection against the targeted disease [ 110 , 111 , 112 ]. While the exact mechanisms are only beginning to be understood, there is emerging evidence that epigenetic mechanisms are involved [ 113 ], including DNA imprinting, as has been shown in HIV and BCG vaccine patient analyses [ 114 , 115 ]. The data from the BCG cohorts indicates that many of these ‘non-specific’ effects can be especially useful, having proven benefit in protecting against autoimmune diseases including multiple sclerosis and type 1 diabetes.…”
Section: Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Vaccines have been shown to have heterologous, or ‘non-specific’ effects, which are additional effects beyond the specific protection against the targeted disease [ 110 , 111 , 112 ]. While the exact mechanisms are only beginning to be understood, there is emerging evidence that epigenetic mechanisms are involved [ 113 ], including DNA imprinting, as has been shown in HIV and BCG vaccine patient analyses [ 114 , 115 ]. The data from the BCG cohorts indicates that many of these ‘non-specific’ effects can be especially useful, having proven benefit in protecting against autoimmune diseases including multiple sclerosis and type 1 diabetes.…”
Section: Designmentioning
confidence: 99%
“…The data from the BCG cohorts indicates that many of these ‘non-specific’ effects can be especially useful, having proven benefit in protecting against autoimmune diseases including multiple sclerosis and type 1 diabetes. Interestingly, the protection conferred accumulates gradually over years [ 115 , 116 , 117 ]. This is especially interesting in light of recent evidence for the transmission of trained immunity in mammals linked to the epigenetic modification of cell lines, termed, ‘trained immunity’ [ 118 ].…”
Section: Designmentioning
confidence: 99%
“…Previous studies attributed the influence of BCG vaccination to immunological as well as metabolic effects [11]. The immune effects include a systemic impact on regulatory T cells, suggesting a role in restoring immune balance [13,26,27]. Hence, we next characterized the regulatory T cell phenotype in age-and sex-matched sub-cohorts of BCG-vaccinated (n = 17) and unvaccinated T1D patients (n = 17) (for demographic characteristics of the sub-cohorts, see Supplementary Table S2).…”
Section: Cd25 Expression On Cd8 + T Cells Is Higher In Bcg-vaccinated...mentioning
confidence: 99%
“…Demethylation of enhancer elements mediated by transcription factors (TFs) binding may allow for a faster response to a secondary infection and thus plays a crucial role in innate immune memory 19 . More recently, studies have shown that BCG vaccination leads to changes in DNA methylation 20 in monocytes and T cells of children 21 . We have previously suggested that DNA methylation changes after BCG vaccination in adults as well 22 , but a comprehensive analysis of the impact of DNA methylation on innate immune memory is missing.…”
Section: Introductionmentioning
confidence: 99%